High-resolution distribution and emission of dimethyl sulfide and its relationship with pCO2 in the Northwest Pacific Ocean - Yan, Shi-Bo; Li, Xiao-Jun; Xu, Feng; Zhang, Hong-Hai; Wang, Jian; Zhang, Yueqi; Yang, Gui-Peng; Zhuang, Guang-Chao; Chen, Zhaohui (Frontiers in Marine Science, 2023)
Ocean-derived dimethyl sulfide (DMS) is widely concerning because of its hypothesized influence on global climate change. This study aims to explore the distribution characteristics and influencing factors of DMS and partial pressure of carbon dioxide (pCO2) in the Northwest Pacific Ocean, as well as the potential relationship between DMS and pCO2. A high-resolution, underway, shipboard measurement device was used to determine the DMS and pCO2 of the surface seawater and atmosphere in the Northwest Pacific and its marginal seas during November 2019. The result show that atmospheric and surface seawater DMS concentrations ranged from 3 to 125 pptv and 0.63 to 2.28 nmol L-1, respectively, with mean values of 46 ± 19 pptv and 1.08 ± 0.34 nmol L-1. The average sea surface pCO2 was 371 ± 16 μatm (range from 332 to 401 μatm). The trends in the surface seawater DMS in different current systems were primarily associated with phytoplankton abundance and composition. Biological activity and physical processes such as cooling jointly influenced the sea surface pCO2. A cold eddy along the transect in the Northwest Pacific Ocean increased DMS at the sea surface by 10% and CO2 uptake by 3%. We found a significant negative correlation between DMS and pCO2 in the Northwest Pacific Ocean at the 0.1° resolution [DMS]seawater = -0.0161[pCO2]seawater + 7.046 (R2 = 0.569, P < 0.01). The DMS and pCO2 sea-air fluxes were estimated to range from 0.04 to 25.3 μmol m-2·d-1 and from -27.0 to 4.22 mmol m-2·d-1 throughout the survey area. The Northwest Pacific Ocean, especially the Oyashio Current, is an important sink of CO2 and a source of DMS.